Cross-culture adaptation and validation of Indonesian language version of Pittsburgh Sleep Quality Index - Fauzi, Achmad; Ahmedy, Fatimah; Rosidah, Rosidah (Intelektual Pustaka Media Utama, 2024)
Hemodialysis (HD) patients have a high rate of poor sleep. The Pittsburgh Sleep Quality Index (PSQI) is the most popular self-reported instrument to measure sleep quality. No study has tested the psychometric efficiency of the Bahasa (Indonesian language) PSQI in hemodialysis (HD) patients, and no cross-cultural adaptation has been done. The purpose of this research was to translate the PSQI into Bahasa and improve its psychometric properties for use in evaluating HD patients in Indonesia. This study used instrument translation, cultural adaptation, content validation, and equivalence to crossculturally validate and adapt an instrument. The hemodialysis center at a West Java medical facility served as a source of potential HD patients throughout the period of October 2022 to February 2023. A content validity index (CVI) was calculated for each item and the entire scale. The factor structure of the Bahasa PSQI has been evaluated by confirmatory factor analysis and internal consistency was calculated using Cronbach's alpha. The online survey received a response rate of 62.8% from a total of 220 patient with HD (about ten responders each item). The level of language clarity was 87.8%, and the level of cultural relevance was 84.5%. The CVI varied from 0.92 to 1.00. Each factor had factor loading ranging from 0.51 to 0.62. that Cronbach alpha for total score was 0.803, and the subscale ranged from 0.771 to 0.863. Our research provides preliminary evidence of the validity and reliability of the translated and adapted tool using data from HD patients in Indonesian hospitals.